The Effect of Scrabble Game To Students’ Vocabulary Mastery at the Eighth Grade Students’ of Mts Daarul Ulum Cihara Lebak - Herawati Herawati; Rizdki Elang Gumelar; Ari Fazria Novari (English Language Education Department, Universitas Majalengka, 2022)
This study aims to determine the effect of the Scrabble game on the vocabulary mastery of class VIII students at Mts Daarul' Ulum Cihara Lebak. This research was conducted at the Daarul'Ulum Cihara school. The population of this study were students of class VIII Mts Darul Ulum Cihara which consisted of two parallel classes. They are class VIII A & VIII B. Each class consists of 25 students. This means that the total population of 50 students is taken as a sample. The data was obtained by giving the text to the students in the experimental and control groups. The data in this study were processed using Microsoft Excel and SPSS 25. The data was analyzed using the t-test formula. This analysis showed that t-count (-24.515) and two-sided significant = 0.000 <0.05. Therefore, the researcher concluded that the scramble game had a significant effect on students' mastery of English vocabulary.